2022
DOI: 10.1007/s11082-022-03876-5
|View full text |Cite
|
Sign up to set email alerts
|

A reduced power budget and enhanced performance in a wdm system: a new fbg apodization function

Abstract: The apodization profiles improve chirped fiber Bragg grating (CFBG) capability to compensate dispersion which enhances the performance of the wavelength division multiplexing (WDM) systems. In this paper, a new apodization profile is proposed to enhance performance and reduces the power budget for a WDM system. The newly apodization profile is implemented to a CFBG as a post compensator in a WDM system for 100 km. It is found the proposed profile enhances the performance and reduces the transmitted power at BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Various research works have been reported on the impact of apodization for obtaining optimal features of FBG specifically for sensing applications [10][11][12]. As compared to such research works, the proposed apodization profile with 25 mm grating length presented in this paper performs slightly better on some specific aspects.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Various research works have been reported on the impact of apodization for obtaining optimal features of FBG specifically for sensing applications [10][11][12]. As compared to such research works, the proposed apodization profile with 25 mm grating length presented in this paper performs slightly better on some specific aspects.…”
Section: Introductionmentioning
confidence: 76%
“…Moreover, a new apodization profile has been proposed to enhance the performance with 50 mm grating length based on a chirped FBG [12]. The simulation outcomes illustrated with the reflectivity, bandwidth, and filter line [12]. The 3 dB bandwidth for the proposed model in this case is comparatively wider than the functional profile of the apodization method proposed in this paper with 25 mm grating length.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…And, the same can be observed by looking at the performance metrics of the system from tables 5 and 6, respectively. Here, we have considered two different functions for the apodization of FBGs, namely the Gaussian and hyperbolic tangent [30,37,38]. To get the optimum response of the system the value of Gauss and tanh parameters are considered as 0.5.…”
Section: Performance Estimation Of the System With The Apodized Fbgs ...mentioning
confidence: 99%
“…The system is designed for longer reach, but the performance of the suggested model is not good with reference to the Qfactor. Mustafa et al [31] suggested a new apodization function with CFBG technique to improve the system performance. In this paper author compared different apodization profiles for 100km length of optical fiber.…”
Section: Literature Reviewmentioning
confidence: 99%